Identification of the novel HLA‐A*31:124 allele by sequence‐based typing in a Chinese cord blood donor. (29th January 2019) - Chen, Nanying; Dong, Lina; Zhang, Wei; He, Ji; Faming, Zhu
Abstract : HLA‐A*31:124 differs from HLA‐A*31:01:02:01 by a single‐nucleotide substitution at position 491 C>G.